Perceptions about the Therapeutic Itinerary after stroke: a qualitative research - Andreza Maria Luzia Baldo de Souza; Rodrigo de Almeida Bastos; Luciane Miranda Guerra; Brunna Verna de Castro Gondinho; Marcelo de Castro Meneghim; Pedro Augusto Thiene Leme (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to analyze the understanding of the Therapeutic Itinerary of people affected by stroke in the Unified Health System context of a medium-sized city in the state of São Paulo. Methods: this is a clinical-qualitative, using in-depth semi-structured interviews, conducted in 2019 with 6 patients, a number determined by theoretical saturation. Results: qualitative content analysis allowed the construction of four categories that emerged from the data: a) You are having a stroke! - Identifying the problem; b) Anguish and expectations in waiting for assistance; c) Helplessness and guidance for rehabilitation after hospital discharge; d) Spirituality in rehabilitation after stroke. Final Considerations: the affected people expressed feelings and meanings, such as fear, anguish, sadness, beliefs and uncertainties, in order to shed light on the complexity inherent to the experiences of Therapeutic Itinerary of stroke.